Teacher training and strategies to develop intra and interpersonal intelligence in classroom - Pedro Sáenz-López Buñuel; E. J. Fernández-Ozcorta; B. J. Almagro Torres; M. A. De Las Heras Pérez (Federación Extremeña de Balonmano; University of Extremadura, 2019)
The education system needs constant adaptations. Teachers and students complain often about the low motivation and the low utility of the competences developed in class. Socio-emotional component requires special attention in young people, so it is necessary educational system serves this demand. Scientific evidence about the benefits of emotional intelligence in the academic performance and well-being of the student is increasingly greater, as well as training needs of teachers. This article shows a educational model based on emotional intelligence starting with teacher training due to their influence in climate classroom.